Composition analysis of Compound Shenhua Tablet, a seven-herb Chinese medicine for IgA nephropathy: evaluation of analyte-capacity of the assays - ZHANG, Haiyan; WANG, Qiuyue; WANG, Jianan; ZHANG, Sichao; JIA, Weiwei; HE, Ning; XIA, Xiaoyan; WANG, Ting; LAI, Liyu; LI, Jiaying; DU, Jing; OLALEYE, Olajide E.; et al. (Chinese journal of natural medicines, 2024)
Compound Shenhua Tablet, a medicine comprising seven herbs, is employed in treating IgA nephropathy. This study aimed to meticulously analyze its chemical composition. Based on a list of candidate compounds, identified through extensive literature review pertinent to the tablet's herbal components, the composition analysis entailed the systematic identification, characterization, and quantification of the constituents. The analyte-capacity of LC/ESI-MS-based and GC/EI-MS-based assays was evaluated. The identified and characterized constituents were quantified to determine their content levels and were ranked based on the constituents' daily doses. A total of 283 constituents, classified into 12 distinct categories, were identified and characterized in the Compound Shenhua Tablet. These constituents exhibited content levels of 1–10 982 μg·g−1, with daily doses of 0.01–395 μmol·d−1. The predominant constituents, with daily doses of ≥ 10 μmol·d−1, include nine organic acids (citric acid, quinic acid, chlorogenic acid, cryptochlorogenic acid, gallic acid, neochlorogenic acid, isochlorogenic acid C, isochlorogenic acid B, and linoleic acid), five iridoids (specnuezhenide, nuezhenoside G13, nuezhenidic acid, secoxyloganin, and secologanoside), two monoterpene glycosides (paeoniflorin and albiflorin), a sesquiterpenoid (curzerenone), a triterpenoid (oleanolic acid), and a phenylethanoid (salidroside). Additionally, there were 83, 126, and 55 constituents detected in the medicine with daily doses of 1–10, 0.1–1, and 0.01–0.1 μmol·d−1, respectively. The combination of the LC/ESI-MS-based and GC/EI-MS-based assays demonstrated a complementary relationship in their analyte-capacity for detecting the constituents present in the medicine. This comprehensive composition analysis establishes a solid foundation for further pharmacological research on Compound Shenhua Tablet and facilitates the quality evaluation of this complex herbal medicine.